Characterization of Colletotrichum graminicola populations from a sorghum hybrid CSH 9 for morphological and pathogenic variability - and V.P. RAO, KUSUM MATHUR, R.P. THAKUR (Indian Phytopathology, 2002)
During a field survey in the 1994 rainy season a popular commercial sorghum hybrid CSH 9 was found showing anthracnose (Coltetotrichum graminicola) symptoms in several farmers’ fields in Maharashtra state of India. About 100 single-lesion isolates obtained from representative leaf samples from four fields of CSH 9 and one field of a local sorghum cultivar (LSC) were characterized and compared for morphological and pathogenic variability. The representative single-lesion isolates and their derivatives varied significantly for morphological traits - colony color, growth pattern, spore size and sporulation rate on oatmeal agar medium. These isolates also exhibited significant variation for latent period, virulence, aggressiveness, and virulence index on a set of sorghum differential lines in a greenhouse test. The isolate from the LSC, although differed morphologically from those of CSH 9, did infect CSH 9 and its parental lines, indicating a virulence shift in the C. graminicola population from the local sorghum to hybrid CSH 9.